CONNECTING COMMUNITIES THROUGH MEDIA: A PATH TO DEVELOPMENT - Sheik Mohamed; Nirmala.M; Ana Mae Monteza; Parwinder Kaur; Hermansyah, Sam (CV. Fahr Publishing, 2024)
The role of media in community development is indispensable in today’s interconnected world. Through traditional and digital forms, media serves as a crucial tool in fostering awareness, participation, inclusivity, and empowerment within communities. This article explores how media contributes to social change, promotes public engagement, and amplifies the voices of marginalized groups. The study highlights the media's influence in strengthening social cohesion and supporting sustainable community development by utilizing secondary data analysis from academic articles, reports from international organizations, government publications, and case studies. The findings underscore the significance of media as a catalyst for positive transformation, enabling communities to address challenges and drive collective progress. Media also plays a vital role in empowering marginalized groups, providing them with a platform to express their concerns. The study demonstrates how media drives social change, enhances public engagement, and reinforces inclusivity in community development, ultimately supporting sustainable development goals.